PERUBAHAN TOTAL GOITER RATE (TGR) ANAK SEKOLAH DI BEBERAPA KABUPATEN DI JAWA BARAT: Kaitannya dengan penggunaan garam beriodium di rumahtangga (THE TOTAL GOITER RATE CHANGES AMONG SCHOOL CHILDREN IN SOME DISTRICTS IN THE PROVINCE OF WEST JAVA: In relat - Basuki Budiman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2010)
ABSTRACT Background: Two national mapping on iodine deficiency problems were conducted in Indonesia in 1996/98 and 2003. The activities covered also iodized salt consumption by household. Universal salt Iodization (USI) is a long-term solution for iodine deficiency disorders, beside of high dose of iodine intervention for short-term solution. Objective: The aim of this article was to evaluate the changes of total goiter rate and the awareness of household using iodized salt, especially in the province of West Java. Methods: The results of the national mapping were evaluated, included the effect of program on the problem.  Results: The mapping found that the situations of the problems were not changed between 1996/98 to 2003. Salt consumption, the way household treated the salt, iodine content in iodized salt were discussed. Conclusions: Iodine status (TGR) of school children in some districts of West Java resulted from national survey were different to local survey due to the time of the survey be conducted. The awareness of people for iodine salt consumption was enough, but not for the dose. [Penel Gizi Makan 2010, 33(2): 117-124]   Keywords: Total Goiter Rate (TGR), school children, iodized salt